IMPLEMENTASI PEMBELAJARAN FISIKA MENGGUNAKAN KEGIATAN LABORATORIUM REAL DAN VIRTUAL UNTUK MENINGKATKAN HASIL BELAJAR PADA POKOK BAHASAN TEORI KINETIC GAS - Febrianti Dwi Lestari; Alex Hariyanto; Sri Handono Budi Prastowo (FKIP Universitas Jember, 2019)
To obtain the purpose of physics learning is needed teoritically learning, nevertheless the existence of learning environment that supports students’ experience directly. This research was conducted is one of Jember Senior High School. In this research, the research subject were students at XI grade Ambulu Senior High School state. The sample which were taken from two classes, such as experimental class 1 which use real laboratory activity and experimental class 2 which use virtual laboratory, by determining the class using random technic sampling. The method of data collection used worksheet instrument as assessment observation of science process skills, and posttest which is formed multiple choice question as learning assessment of cognitive aspect. Then, data was analyzed to determine science process skill and learning assessment using real laboratory activity and virtual laboratory on the subject matter of the kinetic theory of gases which use SPSS 23. Based on the result of analysis data can be conclude that: (1) There was significant differences, science process skills towards physics learning use real and virtual laboratory activities on the subject of the kinetic theory of gases, such as the average score of students’ sciens process skills in grade 1 is higher than it in grade 2. (2) There was significant differences, learning assessment towards physics learning use real and virtual laboratory activities on the subject of the kinetic theory of gases, such as at grade 1 has the criteria for the students learning assessment are high category while at grade 2 has the criteria for the students learning assessment in the medium category.Key word: real laboratory, virtual laboratory, science process skills, learning assessment.